High temperature resistant self-adhesive paint for electromagnetic wire and preparation method thereof
By using epoxy resin and doping nanoboronitride in electromagnetic wire self-adhesive paint, the interfaceability and coordination and coordination are optimized, and the insulation, wear resistance and impact resistance of existing electromagnetic wire self-adhesive paints are solved. The difficulties in coordinating balance have achieved efficient high temperature and weather resistance.
Patent Information
- Application Number
- CN202411579474.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-07
AI Technical Summary
The existing electromagnetic wire self-adhesive paint has difficulties in coordinating and balancing insulation, wear resistance and impact resistance, and has poor high temperature resistance and weather resistance, which limits the efficiency of the product.
Using epoxy resin combined with the balanced modifier, silane coupling agent KH560, durable reinforcement and curing agent, etc., to improve the insulation of the product by optimizing the interface between the raw materials and coordination and coordination. , wear resistance and impact resistance, while enhancing its high temperature resistance.
The electromagnetic wire self-adhesive paint has achieved a coordinated balance between insulation, wear resistance and impact resistance, and significantly improved the product's high temperature resistance, weather resistance and stability, and improved the use efficiency.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electromagnetic wire self-adhesive paint, and in particular to a high temperature resistant self-adhesive paint for electromagnetic wire and a preparation method thereof. Background Art
[0002] Electromagnetic wire is an insulated wire used to make coils or windings in electrical products, also known as winding wire, and self-adhesive paint is traditionally called paint in China. The so-called self-adhesive paint is coated on the surface of the object to be protected or decorated, and can form a continuous film that is firmly attached to the coated object. It is usually a viscous liquid made of resin, oil, or emulsion, with or without pigments, fillers, and corresponding additives, and is prepared with organic solvents or water.
[0003] The existing electromagnetic wire self-adhesive paint adopts organic-inorganic raw materials, and the performance of the self-adhesive paint is enhanced by adding inorganic additives. However, the self-adhesive paint has poor organic-inorganic interface, which easily leads to the difficulty in coordinating and balancing the insulation, wear resistance and impact resistance of the product, limiting the use efficiency of the product. At the same time, the product has poor high temperature resistance, weather resistance and durability stability, which further limits the use efficiency of the product. Based on this, the present invention further improves it. Summary of the invention
[0004] In view of the defects of the prior art, the purpose of the present invention is to provide a high temperature resistant self-adhesive paint for electromagnetic wire and a preparation method thereof, so as to solve the problems raised in the above background technology.
[0005] The present invention solves the technical problem by adopting the following technical solution:
[0006] The present invention provides a high temperature resistant self-adhesive paint for electromagnetic wire, comprising the following raw materials in parts by weight:
[0007] 40-45 parts of epoxy resin, 8-12 parts of balance modifier mixed with nano boron nitride, 5-7 parts of silane coupling agent KH560, 4-6 parts of durable reinforcing agent, 3-5 parts of dispersant, 3-5 parts of thickener, 5-8 parts of curing agent, and 20-25 parts of water.
[0008] Preferably, the epoxy resin is bisphenol A epoxy resin; the curing agent is ethylenediamine; the dispersant is sodium polyacrylate dispersant; and the thickener is carboxymethyl cellulose.
[0009] Preferably, the preparation method of the balance modifier doped with nano-boron nitride is:
[0010] S01: irradiate the nano boron nitride in a proton irradiation box, the irradiation power is 350-400W, the irradiation time is 2-5min, and the irradiation ends;
[0011] The irradiated nano-boron nitride and a sodium silicate solution having a mass fraction of 4 to 6% are mixed in a weight ratio of 2:5 to obtain a nano-boron nitride liquid;
[0012] S02: Ultrasonic mixing of nano calcium carbonate, lanthanum chloride solution and silicon powder in a weight ratio of 3: (5-7): 1 is performed, and the ultrasonic mixing is terminated to obtain a modified additive;
[0013] S03: adding 3 to 5 parts of the modified additive to 4 to 7 parts of dimethylhydroxy silicone oil, and then adding 1 to 3 parts of silane coupling agent KH550 and 2 to 4 parts of chitosan solution, blending and stirring sufficiently to obtain a balance regulator;
[0014] S04: Mix the nano-boron nitride liquid and the balance regulator in a weight ratio of 5:3 and perform ball milling. After the ball milling is completed, wash with water and dry to obtain a balance modifier mixed with nano-boron nitride.
[0015] Preferably, the ultrasonic power of the ultrasonic mixing treatment is 350-400W, and the ultrasonic time is 20-30min; the ball milling speed of the mixing ball milling treatment is 1000-1500r / min, and the ball milling is 1h.
[0016] The mass fraction of the chitosan solution is 4-7%; the mass fraction of the lanthanum chloride solution is 2-5%.
[0017] Preferably, the preparation method of the durable reinforcing agent is:
[0018] S11: preheating the hollow glass microspheres at 55-60° C. for 10-15 min, and then mixing the preheated hollow glass microspheres, yttrium nitrate solution, and sodium citrate solution in a weight ratio of (3-4):1:(5-7) to obtain a modified hollow glass microsphere agent;
[0019] S12: The reinforcing agent and the modified hollow glass microsphere are mixed and ball-milled in a weight ratio of 3:(5-8) at a ball-milling speed of 1000-1500 r / min for 2 hours. After the ball-milling is completed, the mixture is washed with water and dried to obtain a durable reinforcing agent.
[0020] Preferably, the mass fraction of the yttrium nitrate solution is 2-5%; the mass fraction of the sodium citrate solution is 5-7%.
[0021] Preferably, the preparation method of the complementary enhancer is:
[0022] Immerse wollastonite in a sufficient amount of 5% by mass zinc sulfate solution and stir and immerse for treatment, after stirring, wash with water and dry to obtain wollastonite agent;
[0023] 3-5 parts of diatomaceous earth and 1-3 parts of strontium oxide are added to 4-7 parts of 4-6% dopamine hydrochloride solution and stirred to mix thoroughly. Subsequently, 2-3 parts of wollastonite are added and the mixture is ball-milled thoroughly. The ball-milling speed is 1500r / min and the ball-milling is performed for 1h. After the ball-milling is completed, the mixture is washed with water and dried to obtain a complementary enhancer.
[0024] Preferably, the stirring speed of the stirring immersion treatment is 550 to 750 r / min, and the stirring time is 20 to 30 min.
[0025] The present invention also provides a method for preparing a high temperature resistant self-adhesive paint for electromagnetic wire, comprising the following steps:
[0026] The raw materials are weighed according to weight, epoxy resin, a balance modifier mixed with nano boron nitride, a silane coupling agent KH560, a durable reinforcing agent, a dispersant, carboxymethyl cellulose and water are uniformly mixed, and finally a curing agent is added to obtain the high temperature resistant self-adhesive paint of the present invention.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] The electromagnetic wire high temperature resistant self-adhesive paint of the present invention adopts epoxy resin, silane coupling agent KH560, dispersant, thickener and curing agent as raw materials. The added silane coupling agent KH560 optimizes the interface between the raw materials and improves the interface bonding effect between the raw materials. At the same time, the balanced modifier and the durable reinforcing agent added with nano-boron nitride are coordinated and matched, and the insulation, wear resistance and impact resistance of the product are coordinated and improved. At the same time, the product has significant effects on high temperature resistance, weather resistance and durability stability; the balanced modifier added with nano-boron nitride uses nano-boron nitride to irradiate in a proton irradiation box to optimize the active efficiency of boron nitride, and obtains nano-boron nitride liquid by mixing and proportioning sodium silicate solution, and obtains modified additives by coordinated matching of nano-calcium carbonate, lanthanum chloride solution and silicon micropowder. The nano-boron nitride is synergistically strengthened by the coordination and matching between nano-calcium carbonate and silicon micropowder to enhance the stability of nano-boron nitride. The insulation, wear resistance and impact resistance of the strong product system are improved in coordination. At the same time, the modified additives are coordinated with silane coupling agent KH550 and chitosan solution, and the raw materials are improved by blending the balanced modifiers with nano-boron nitride, so that the performance of the product is further improved. The durable reinforcing agent is hollow glass microspheres preheated at 55-60°C for 10-15 minutes, and then the preheated hollow glass microspheres, yttrium nitrate solution and sodium citrate solution are blended and coordinated. Through the common coordination and synergy between the raw materials, the wollastonite added at the same time is immersed in a sufficient amount of 5% by mass zinc sulfate solution and stirred and immersed. Wollastonite is used to immerse in zinc sulfate solution, and then diatomaceous earth, strontium oxide and dopamine hydrochloride solution are blended and coordinated. Through the common synergy between the raw materials, the balance between the performances is further enhanced, and the high temperature resistance, weather resistance and durability stability of the product are improved. DETAILED DESCRIPTION
[0029] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] The high temperature resistant self-adhesive paint for electromagnetic wire of this embodiment includes the following raw materials in parts by weight:
[0031] 40-45 parts of epoxy resin, 8-12 parts of balance modifier mixed with nano boron nitride, 5-7 parts of silane coupling agent KH560, 4-6 parts of durable reinforcing agent, 3-5 parts of dispersant, 3-5 parts of thickener, 5-8 parts of curing agent, and 20-25 parts of water.
[0032] The epoxy resin in this embodiment is bisphenol A epoxy resin; the curing agent is ethylenediamine; the dispersant is sodium polyacrylate dispersant; and the thickener is carboxymethyl cellulose.
[0033] The preparation method of the balanced modifier doped with nano-boron nitride in this embodiment is as follows:
[0034] S01: irradiate the nano boron nitride in a proton irradiation box, the irradiation power is 350-400W, the irradiation time is 2-5min, and the irradiation ends;
[0035] The irradiated nano-boron nitride and a sodium silicate solution having a mass fraction of 4 to 6% are mixed in a weight ratio of 2:5 to obtain a nano-boron nitride liquid;
[0036] S02: Ultrasonic mixing of nano calcium carbonate, lanthanum chloride solution and silicon powder in a weight ratio of 3: (5-7): 1 is performed, and the ultrasonic mixing is terminated to obtain a modified additive;
[0037] S03: adding 3 to 5 parts of the modified additive to 4 to 7 parts of dimethylhydroxy silicone oil, and then adding 1 to 3 parts of silane coupling agent KH550 and 2 to 4 parts of chitosan solution, blending and stirring sufficiently to obtain a balance regulator;
[0038] S04: Mix the nano-boron nitride liquid and the balance regulator in a weight ratio of 5:3 and perform ball milling. After the ball milling is completed, wash with water and dry to obtain a balance modifier mixed with nano-boron nitride.
[0039] The ultrasonic power of the ultrasonic mixing treatment in this embodiment is 350-400W, and the ultrasonic time is 20-30min; the ball milling speed of the mixing ball milling treatment is 1000-1500r / min, and the ball milling is 1h.
[0040] The mass fraction of the chitosan solution is 4-7%; the mass fraction of the lanthanum chloride solution is 2-5%.
[0041] The preparation method of the durable reinforcing agent of this embodiment is:
[0042] S11: preheating the hollow glass microspheres at 55-60° C. for 10-15 min, and then mixing the preheated hollow glass microspheres, yttrium nitrate solution, and sodium citrate solution in a weight ratio of (3-4):1:(5-7) to obtain a modified hollow glass microsphere agent;
[0043] S12: The reinforcing agent and the modified hollow glass microsphere are mixed and ball-milled in a weight ratio of 3:(5-8) at a ball-milling speed of 1000-1500 r / min for 2 hours. After the ball-milling is completed, the mixture is washed with water and dried to obtain a durable reinforcing agent.
[0044] The mass fraction of the yttrium nitrate solution in this embodiment is 2-5%; the mass fraction of the sodium citrate solution is 5-7%.
[0045] The preparation method of the complementary enhancing agent of this embodiment is:
[0046] Immerse wollastonite in a sufficient amount of 5% by mass zinc sulfate solution and stir and immerse for treatment, after stirring, wash with water and dry to obtain wollastonite agent;
[0047] 3-5 parts of diatomaceous earth and 1-3 parts of strontium oxide are added to 4-7 parts of 4-6% dopamine hydrochloride solution and stirred to mix thoroughly. Subsequently, 2-3 parts of wollastonite are added and the mixture is ball-milled thoroughly. The ball-milling speed is 1500r / min and the ball-milling is performed for 1h. After the ball-milling is completed, the mixture is washed with water and dried to obtain a complementary enhancer.
[0048] The stirring speed of the stirring immersion treatment in this embodiment is 550 to 750 r / min, and the stirring time is 20 to 30 min.
[0049] A method for preparing a high temperature resistant self-adhesive paint for electromagnetic wire in this embodiment comprises the following steps:
[0050] The raw materials are weighed according to weight, epoxy resin, a balance modifier mixed with nano boron nitride, a silane coupling agent KH560, a durable reinforcing agent, a dispersant, carboxymethyl cellulose and water are uniformly mixed, and finally a curing agent is added to obtain the high temperature resistant self-adhesive paint of the present invention.
[0051] Example 1
[0052] The high temperature resistant self-adhesive paint for electromagnetic wire of this embodiment includes the following raw materials in parts by weight:
[0053] 40 parts of epoxy resin, 8 parts of balance modifier mixed with nano-boron nitride, 5 parts of silane coupling agent KH560, 4 parts of durable reinforcing agent, 3 parts of dispersant, 3 parts of thickener, 5 parts of curing agent, and 20 parts of water.
[0054] The epoxy resin in this embodiment is bisphenol A epoxy resin; the curing agent is ethylenediamine; the dispersant is sodium polyacrylate dispersant; and the thickener is carboxymethyl cellulose.
[0055] The preparation method of the balanced modifier doped with nano-boron nitride in this embodiment is as follows:
[0056] S01: irradiate the nano boron nitride in a proton irradiation box, the irradiation power is 350W, the irradiation time is 2 minutes, and the irradiation ends;
[0057] The irradiated nano-boron nitride and 4% by mass sodium silicate solution are mixed in a weight ratio of 2:5 to obtain a nano-boron nitride liquid;
[0058] S02: Ultrasonic mixing of nano-calcium carbonate, lanthanum chloride solution and silicon powder according to a weight ratio of 3:5:1, and the ultrasonic mixing is terminated to obtain a modified additive;
[0059] S03: adding 3 parts of the modified additive to 4 parts of dimethylhydroxy silicone oil, and then adding 1 part of silane coupling agent KH550 and 2 parts of chitosan solution, blending and stirring sufficiently to obtain a balance regulator;
[0060] S04: Mix the nano-boron nitride liquid and the balance regulator in a weight ratio of 5:3 and perform ball milling. After the ball milling is completed, wash with water and dry to obtain a balance modifier mixed with nano-boron nitride.
[0061] The ultrasonic power of the ultrasonic mixing treatment in this embodiment is 350W, and the ultrasonic time is 20min; the ball milling speed of the mixing ball milling treatment is 1000r / min, and the ball milling is 1h.
[0062] The mass fraction of the chitosan solution is 4%; the mass fraction of the lanthanum chloride solution is 2%.
[0063] The preparation method of the durable reinforcing agent of this embodiment is:
[0064] S11: preheating the hollow glass microspheres at 55° C. for 10 min, and then mixing the preheated hollow glass microspheres, yttrium nitrate solution, and sodium citrate solution in a weight ratio of 3:1:5 to obtain a modified hollow glass microsphere agent;
[0065] S12: The reinforcing agent and the modified hollow glass microsphere are mixed in a weight ratio of 3:5 and ball-milled at a speed of 1000 r / min for 2 h. After the ball milling is completed, the mixture is washed with water and dried to obtain a durable reinforcing agent.
[0066] The mass fraction of the yttrium nitrate solution in this embodiment is 2%; the mass fraction of the sodium citrate solution is 5%.
[0067] The preparation method of the complementary enhancing agent of this embodiment is:
[0068] Immerse wollastonite in a sufficient amount of 5% by mass zinc sulfate solution and stir and immerse for treatment, after stirring, wash with water and dry to obtain wollastonite agent;
[0069] Add 3 parts of diatomaceous earth and 1 part of strontium oxide to 4 parts of 4% by mass dopamine hydrochloride solution and stir to mix thoroughly, then add 2 parts of wollastonite agent and blend thoroughly with ball mill at a ball milling speed of 1500r / min for 1h. After the ball milling is completed, wash with water and dry to obtain a complementary enhancer.
[0070] The stirring speed of the stirring immersion treatment in this embodiment is 550 r / min, and the stirring time is 20 min.
[0071] A method for preparing a high temperature resistant self-adhesive paint for electromagnetic wire in this embodiment comprises the following steps:
[0072] The raw materials are weighed according to weight, epoxy resin, a balance modifier mixed with nano boron nitride, a silane coupling agent KH560, a durable reinforcing agent, a dispersant, carboxymethyl cellulose and water are uniformly mixed, and finally a curing agent is added to obtain the high temperature resistant self-adhesive paint of the present invention.
[0073] Example 2
[0074] The high temperature resistant self-adhesive paint for electromagnetic wire of this embodiment includes the following raw materials in parts by weight:
[0075] 45 parts of epoxy resin, 12 parts of balance modifier mixed with nano-boron nitride, 7 parts of silane coupling agent KH560, 6 parts of durable reinforcing agent, 5 parts of dispersant, 5 parts of thickener, 8 parts of curing agent, and 25 parts of water.
[0076] The epoxy resin in this embodiment is bisphenol A epoxy resin; the curing agent is ethylenediamine; the dispersant is sodium polyacrylate dispersant; and the thickener is carboxymethyl cellulose.
[0077] The preparation method of the balanced modifier doped with nano-boron nitride in this embodiment is as follows:
[0078] S01: irradiate the nano boron nitride in a proton irradiation box, the irradiation power is 400W, the irradiation time is 5 minutes, and the irradiation ends;
[0079] The irradiated nano-boron nitride and a 6% by mass sodium silicate solution are mixed in a weight ratio of 2:5 to obtain a nano-boron nitride liquid;
[0080] S02: Ultrasonic mixing of nano-calcium carbonate, lanthanum chloride solution and silicon powder according to a weight ratio of 3:7:1, and the ultrasonic mixing is terminated to obtain a modified additive;
[0081] S03: adding 5 parts of the modified additive to 7 parts of dimethylhydroxy silicone oil, and then adding 3 parts of silane coupling agent KH550 and 4 parts of chitosan solution, blending and stirring sufficiently to obtain a balance regulator;
[0082] S04: Mix the nano-boron nitride liquid and the balance regulator in a weight ratio of 5:3 and perform ball milling. After the ball milling is completed, wash with water and dry to obtain a balance modifier mixed with nano-boron nitride.
[0083] The ultrasonic power of the ultrasonic mixing treatment in this embodiment is 400 W, and the ultrasonic time is 30 min; the ball milling speed of the mixing ball milling treatment is 1500 r / min, and the ball milling is 1 h.
[0084] The mass fraction of the chitosan solution is 7%; the mass fraction of the lanthanum chloride solution is 5%.
[0085] The preparation method of the durable reinforcing agent of this embodiment is:
[0086] S11: preheating the hollow glass microspheres at 60° C. for 15 min, and then mixing the preheated hollow glass microspheres, yttrium nitrate solution, and sodium citrate solution in a weight ratio of 4:1:7 to obtain a modified hollow glass microsphere agent;
[0087] S12: The reinforcing agent and the modified hollow glass microsphere are mixed in a weight ratio of 3:8 and ball-milled at a speed of 1500 r / min for 2 h. After the ball milling is completed, the mixture is washed with water and dried to obtain a durable reinforcing agent.
[0088] The mass fraction of the yttrium nitrate solution in this embodiment is 5%; the mass fraction of the sodium citrate solution is 7%.
[0089] The preparation method of the complementary enhancing agent of this embodiment is:
[0090] Immerse wollastonite in a sufficient amount of 5% by mass zinc sulfate solution and stir and immerse for treatment, after stirring, wash with water and dry to obtain wollastonite agent;
[0091] Add 5 parts of diatomaceous earth and 3 parts of strontium oxide to 7 parts of 6% dopamine hydrochloride solution and stir to mix thoroughly, then add 3 parts of wollastonite agent and blend thoroughly with ball mill at a ball milling speed of 1500r / min for 1h. After the ball milling is completed, wash with water and dry to obtain a complementary enhancer.
[0092] The stirring speed of the stirring immersion treatment in this embodiment is 750 r / min, and the stirring time is 30 min.
[0093] A method for preparing a high temperature resistant self-adhesive paint for electromagnetic wire in this embodiment comprises the following steps:
[0094] The raw materials are weighed according to weight, epoxy resin, a balance modifier mixed with nano boron nitride, a silane coupling agent KH560, a durable reinforcing agent, a dispersant, carboxymethyl cellulose and water are uniformly mixed, and finally a curing agent is added to obtain the high temperature resistant self-adhesive paint of the present invention.
[0095] Example 3
[0096] The high temperature resistant self-adhesive paint for electromagnetic wire of this embodiment includes the following raw materials in parts by weight:
[0097] 42.5 parts of epoxy resin, 10 parts of balance modifier blended with nano-boron nitride, 6 parts of silane coupling agent KH560, 5 parts of durable reinforcing agent, 4 parts of dispersant, 4 parts of thickener, 6.5 parts of curing agent, and 22.5 parts of water.
[0098] The epoxy resin in this embodiment is bisphenol A epoxy resin; the curing agent is ethylenediamine; the dispersant is sodium polyacrylate dispersant; and the thickener is carboxymethyl cellulose.
[0099] The preparation method of the balanced modifier doped with nano-boron nitride in this embodiment is as follows:
[0100] S01: irradiate the nano boron nitride in a proton irradiation box, the irradiation power is 375W, the irradiation time is 3.5min, and the irradiation ends;
[0101] The irradiated nano-boron nitride and a 5% by mass sodium silicate solution are mixed in a weight ratio of 2:5 to obtain a nano-boron nitride liquid;
[0102] S02: Ultrasonic mixing of nano calcium carbonate, lanthanum chloride solution and silicon powder in a weight ratio of 3:4:1, and the ultrasonic mixing is terminated to obtain a modified additive;
[0103] S03: adding 4 parts of the modified additive to 5.5 parts of dimethylhydroxy silicone oil, and then adding 2 parts of silane coupling agent KH550 and 3 parts of chitosan solution, blending and stirring sufficiently to obtain a balance regulator;
[0104] S04: Mix the nano-boron nitride liquid and the balance regulator in a weight ratio of 5:3 and perform ball milling. After the ball milling is completed, wash with water and dry to obtain a balance modifier mixed with nano-boron nitride.
[0105] The ultrasonic power of the ultrasonic mixing treatment in this embodiment is 370W, and the ultrasonic time is 25min; the ball milling speed of the mixing ball milling treatment is 1250r / min, and the ball milling is 1h.
[0106] The mass fraction of the chitosan solution is 5.5%; the mass fraction of the lanthanum chloride solution is 3.5%.
[0107] The preparation method of the durable reinforcing agent of this embodiment is:
[0108] S11: preheating the hollow glass microspheres at 57° C. for 12.5 min, and then mixing the preheated hollow glass microspheres, yttrium nitrate solution, and sodium citrate solution in a weight ratio of 3.5:1:6 to obtain a modified hollow glass microsphere agent;
[0109] S12: The reinforcing agent and the modified hollow glass microsphere are mixed in a weight ratio of 3:6.5, and the mixture is ball-milled at a speed of 1250 r / min for 2 h. After the ball-milling is completed, the mixture is washed with water and dried to obtain a durable reinforcing agent.
[0110] The mass fraction of the yttrium nitrate solution in this embodiment is 3.5%; the mass fraction of the sodium citrate solution is 6%.
[0111] The preparation method of the complementary enhancing agent of this embodiment is:
[0112] Immerse wollastonite in a sufficient amount of 5% by mass zinc sulfate solution and stir and immerse for treatment, after stirring, wash with water and dry to obtain wollastonite agent;
[0113] 4 parts of diatomaceous earth and 2 parts of strontium oxide are added to 5.5 parts of 5% by mass dopamine hydrochloride solution and stirred to mix thoroughly. Then, 2.5 parts of wollastonite are added and the mixture is ball-milled thoroughly. The ball-milling speed is 1500 r / min and the ball-milling is performed for 1 hour. After the ball-milling is completed, the mixture is washed with water and dried to obtain a complementary enhancer.
[0114] The stirring speed of the stirring immersion treatment in this embodiment is 600 r / min, and the stirring time is 25 min.
[0115] A method for preparing a high temperature resistant self-adhesive paint for electromagnetic wire in this embodiment comprises the following steps:
[0116] The raw materials are weighed according to weight, epoxy resin, a balance modifier mixed with nano boron nitride, a silane coupling agent KH560, a durable reinforcing agent, a dispersant, carboxymethyl cellulose and water are uniformly mixed, and finally a curing agent is added to obtain the high temperature resistant self-adhesive paint of the present invention.
[0117] Comparative Example 1
[0118] The difference from Example 3 is that no balance modifier for mixing nano boron nitride is added.
[0119] Comparative Example 2
[0120] The difference from Example 3 is that in the preparation of the balance modifier blended with nano-boron nitride, nano-boron nitride liquid is replaced by nano-boron nitride.
[0121] Comparative Example 3
[0122] The difference from Example 3 is that no balance regulator is added in the preparation of the balance modifier blended with nano-boron nitride.
[0123] Comparative Example 4
[0124] The difference from Example 3 is that no modifying additive is added in the preparation of the balance regulator.
[0125] Comparative Example 5
[0126] The difference from Example 3 is that no nano calcium carbonate or silicon powder is added to the modified additive.
[0127] Comparative Example 6
[0128] The difference from Example 3 is that no silane coupling agent KH550 or chitosan solution is added to the balance regulator.
[0129] Comparative Example 7
[0130] The difference from Example 3 is that no durable reinforcing agent is added.
[0131] Comparative Example 8
[0132] The difference from Example 3 is that no modified hollow glass microsphere agent is added in the preparation of the durable reinforcing agent.
[0133] Comparative Example 9
[0134] The difference from Example 3 is that no preheated hollow glass microspheres are added in the preparation of the modified hollow glass microsphere agent.
[0135] Comparative Example 10
[0136] The difference from Example 3 is that no reinforcing agent is added in the preparation of the durable reinforcing agent.
[0137] The product performance of Examples 1-3 and Comparative Examples 1-10 was tested. The products were placed at 65°C for 12 hours, and then placed in a UV aging box with a UV wavelength of 313nm and an irradiance of 0.5W / m for 24 hours. The above is one cycle. The test was repeated 10 times. The performance measurement results are as follows:
[0138] Table 1
[0139]
[0140] It can be concluded from Examples 1-3 and Comparative Examples 1-10 that the product of Example 3 of the present invention has excellent breakdown strength, wear resistance and impact performance under normal conditions, the performance of the product can achieve balanced and coordinated improvements, and the product has significant performance stability under high temperature and weather resistance conditions.
[0141] If neither the balance modifier for adjusting nano-boron nitride nor the durable reinforcing agent is added to the product, the performance of the product will deteriorate significantly. The synergistic effect of the two will be the most obvious.
[0142] In the preparation of the balance modifier blended with nano-boron nitride, nano-boron nitride liquid is replaced by nano-boron nitride, no balance regulator is added in the preparation of the balance modifier blended with nano-boron nitride, no modifying additive is added in the preparation of the balance regulator, nano-calcium carbonate and silicon powder are not added to the modifying additive, and silane coupling agent KH550 and chitosan solution are not added to the balance modifier. The performance of the balance modifier blended with nano-boron nitride obtained by different methods has a tendency to deteriorate. The performance effect of the balance modifier blended with nano-boron nitride obtained by using the balance regulator obtained by using the specific modifying additive of the present invention and the nano-boron nitride liquid is the most significant.
[0143] When the modified hollow glass microsphere agent is not added in the preparation of the durable reinforcing agent, the preheated hollow glass microspheres are not added in the preparation of the modified hollow glass microsphere agent, and the complementary emphasizing agent is not added in the preparation of the durable reinforcing agent, the performance of the product tends to deteriorate, and when the complementary emphasizing agent is not added, the performance of the product deteriorates significantly. The modified hollow glass microsphere agent obtained by the specific method of the present invention is combined with the complementary emphasizing agent, and the performance effect of the product is the most significant. The use of other methods instead is not as significant as the durable reinforcing agent of the present invention.
[0144] Since the tonic enhancer has a significant impact on the performance of the product, further research is conducted on this:
[0145] The preparation method of the tonic enhancer is as follows:
[0146] Immerse wollastonite in a sufficient amount of 5% by mass zinc sulfate solution and stir and immerse for treatment, after stirring, wash with water and dry to obtain wollastonite agent;
[0147] 4 parts of diatomaceous earth and 2 parts of strontium oxide are added to 5.5 parts of 5% by mass dopamine hydrochloride solution and stirred to mix thoroughly. Then, 2.5 parts of wollastonite are added and the mixture is ball-milled thoroughly. The ball-milling speed is 1500 r / min and the ball-milling is performed for 1 hour. After the ball-milling is completed, the mixture is washed with water and dried to obtain a complementary enhancer.
[0148] Experimental Example 1
[0149] The only difference from Example 3 is that no wollastonite agent is added in the preparation of the complementary enhancing agent.
[0150] Experimental Example 2
[0151] The only difference from Example 3 is that the wollastonite agent is replaced by wollastonite.
[0152] Experimental Example 3
[0153] The only difference from Example 3 is that diatomaceous earth is not added in the preparation of the complement enhancing agent.
[0154] Experimental Example 4
[0155] The only difference from Example 3 is that no strontium oxide is added in the preparation of the complementary enhancer.
[0156] Experimental Example 5
[0157] The only difference from Example 3 is that the dopamine hydrochloride solution is replaced by deionized water.
[0158] Table 2
[0159]
[0160] It can be seen from Experimental Examples 1-5 that wollastonite was not added in the preparation of the complementary enhancer, and the performance of the product had the greatest impact on the preparation of the complementary enhancer, followed by the fact that diatomaceous earth was not added. At the same time, the wollastonite agent was replaced by wollastonite, strontium oxide was not added in the preparation of the complementary enhancer, and deionized water was used instead of the dopamine hydrochloride solution. The complementary enhancers obtained by different methods all had a trend of worsening performance. The process steps and raw materials in the preparation of the complementary enhancer are indispensable. The complementary enhancers obtained by other methods are not as significant as the effects of the present invention.
[0161] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0162] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A high temperature resistant self-adhesive paint for electromagnetic wire, characterized in that: It includes the following raw materials in parts by weight: 40-45 parts of epoxy resin, 8-12 parts of balance modifier mixed with nano boron nitride, 5-7 parts of silane coupling agent KH560, 4-6 parts of durable reinforcing agent, 3-5 parts of dispersant, 3-5 parts of thickener, 5-8 parts of curing agent, and 20-25 parts of water; The preparation method of the balance modifier doped with nano boron nitride is as follows: S01: irradiate the nano boron nitride in a proton irradiation box, the irradiation power is 350-400W, the irradiation lasts for 2-5 minutes, and the irradiation ends; The irradiated nano-boron nitride and a sodium silicate solution having a mass fraction of 4 to 6% are mixed in a weight ratio of 2:5 to obtain a nano-boron nitride liquid; S02: Ultrasonic mixing of nano calcium carbonate, lanthanum chloride solution and silicon powder in a weight ratio of 3: (5-7): 1 is performed, and the ultrasonic mixing is terminated to obtain a modified additive; S03: adding 3 to 5 parts of the modified additive to 4 to 7 parts of dimethylhydroxy silicone oil, and then adding 1 to 3 parts of silane coupling agent KH550 and 2 to 4 parts of chitosan solution, blending and stirring sufficiently to obtain a balance regulator; S04: mixing the nano boron nitride liquid and the balance modifier in a weight ratio of 5:3 and subjecting them to ball milling. After the ball milling is completed, washing and drying are performed to obtain a balance modifier mixed with nano boron nitride; The preparation method of the durable reinforcing agent is: S11: preheating the hollow glass microspheres at 55-60° C. for 10-15 min, and then mixing the preheated hollow glass microspheres, yttrium nitrate solution, and sodium citrate solution in a weight ratio of (3-4):1:(5-7) to obtain a modified hollow glass microsphere agent; S12: mixing the reinforcing agent and the modified hollow glass microsphere agent in a weight ratio of 3:(5-8) and subjecting them to ball milling at a ball milling speed of 1000-1500 r / min for 2 h. After the ball milling is completed, washing with water and drying are performed to obtain a durable reinforcing agent; The preparation method of the complementary enhancer is as follows: Immerse wollastonite in a sufficient amount of 5% by mass zinc sulfate solution and stir and immerse for treatment, after stirring, wash with water and dry to obtain wollastonite agent; 3-5 parts of diatomaceous earth and 1-3 parts of strontium oxide are added to 4-7 parts of 4-6% dopamine hydrochloride solution and stirred to mix thoroughly. Subsequently, 2-3 parts of wollastonite are added and the mixture is ball-milled thoroughly. The ball-milling speed is 1500r / min and the ball-milling is performed for 1h. After the ball-milling is completed, the mixture is washed with water and dried to obtain a complementary enhancer.
2. The high temperature resistant self-adhesive paint for electromagnetic wire according to claim 1, characterized in that: The epoxy resin is bisphenol A epoxy resin; the curing agent is ethylenediamine; the dispersant is sodium polyacrylate dispersant; and the thickener is carboxymethyl cellulose.
3. The high temperature resistant self-adhesive paint for electromagnetic wire according to claim 1, characterized in that: The ultrasonic power of the ultrasonic mixing treatment is 350-400W, and the ultrasonic time is 20-30min; the ball milling speed of the mixing ball milling treatment is 1000-1500r / min, and the ball milling is 1h.
4. The high temperature resistant self-adhesive paint for electromagnetic wire according to claim 1, characterized in that: The mass fraction of the chitosan solution is 4-7%; the mass fraction of the lanthanum chloride solution is 2-5%.
5. The high temperature resistant self-adhesive paint for electromagnetic wire according to claim 1, characterized in that: The mass fraction of the yttrium nitrate solution is 2-5%; the mass fraction of the sodium citrate solution is 5-7%.
6. The high temperature resistant self-adhesive paint for electromagnetic wire according to claim 1, characterized in that: The stirring speed of the stirring immersion treatment is 550-750 r / min, and the stirring time is 20-30 min.
7. A method for preparing a high temperature resistant self-adhesive paint for electromagnetic wire according to any one of claims 1 to 6, characterized in that: The following steps are involved: The raw materials are weighed according to weight, and the epoxy resin, the balance modifier mixed with nano-boron nitride, the silane coupling agent KH560, the durable reinforcing agent, the dispersant, the carboxymethyl cellulose and water are uniformly mixed, and finally a curing agent is added to obtain a high temperature resistant self-adhesive paint.
Citation Information
Patent Citations
Epoxy group heat conduction adhesive and preparation method thereof
CN113429924A
Coating-modifying agent and heavy duty coating composition
JP2001115078A